Online Fraud Victimization in China: A Case Study of Baidu Tieba - Lee, Claire Seungeun (Victims & offenders, 2021)
When it comes to online populations and markets, China has some of the largest in the world. As a result, Chinese cybercriminals have more opportunities to target and access victims. While extant research in Western countries has examined online fraud victimization and offenses in virtual communities, a relatively small body of research on these phenomena has been conducted in non-Western societies. This study attempts to address this gap by analyzing online fraud victimization in Chinese online communities. Routine activity theory is applied to understand the patterns and dynamics of victimization. Data were collected from Baidu Tieba (a Chinese version of Craigslist), a prominent Chinese online platform for reporting victimization. This study highlights the range of services, types, and methods along which victimization occurs. The results, which reflect China’s rapid pace of technological development, show that different types of fraud are perpetrated online and that victimization methods are associated with particular types of media. This study also identifies implications for China and other countries where similar crimes and instances in cyberspace occur.